Change on the Brain? The Neuroscience of Organizational Transformation (International Journal of Applied Research in Management and Economics, 2024)
True transformations aim to change the core identity of an organization, are often disruptive, and rarely result in their intended outcomes. The objective of this paper is to propose a theoretical approach for more effective transformations via the syntheses of emerging findings in managerial science, organizational psychology, and social cognitive neuroscience. The authored conducted a literature review of traditional methods and the application of neuroscience to organizational transformation, proposing that consideration to leader and employee neuroanatomy can significantly impact transformation success. The emergent five-phase approach - Exploration & Discovery, Surfacing & Co-Creation, Enablement & Prioritization, Implementation, and Empowerment - integrates practices informed by neuroscience to enhance leadership alignment, employee engagement, and change sustainability. By focusing on activities such as vision alignment, co-creation, and leadership development, the approach seeks to optimize brain functions related to trust, motivation, and adaptability. Neuroscientific concepts like neural synchrony, hormone and neurotransmitter release, and specific neural circuit activations are utilized to improve team dynamics, decision-making, and learning. This neuro-informed approach challenges conventional practices by emphasizing co-creative solutioning with employees, piloting programs, and empowering middle managers to lead transformation efforts. Data from case studies demonstrate significant improvements in employee experience and sustainable shifts in organizational behavior. The paper concludes with a call for further research to solidify the emerging intersection of neuroscience and organizational transformation.